A retrospective review of facility-level obstetric complications and stillbirths in southern Haiti, 2013 - 2016 - Alka Dev; Keegan O'Hern; Joseph Yves Domerçant; Gerard Lucien; Lucie Lafortune; Reynold Grand-Pierre; Peter F. Wright (Pan American Health Organization, 2019)
Objective. To assess the incidence of obstetric complications-eclampsia, dystocia, cesarean section, postpartum hemorrhage, and stillbirths-in hospitals in southern Haiti in 2013 - 2016 and to discuss implications for improvements to the surveillance of birth outcomes. Methods. This was a cross-sectional, retrospective study of data for 32 442 deliveries recorded in 2013 - 2016 by the Integrated Monitoring, Evaluation, and Surveillance System for facilities across three departments and one high-volume hospital in southern Haiti. Annual incidence rates of eclampsia, dystocia, cesarean section, postpartum hemorrhage, and stillbirths (both macerated and fresh) were calculated. Results. The incidence of eclampsia in the study sample was 2% - 3% and of dystocia approximately 5%, comparable to elsewhere in Haiti and other low-income countries. Cesarean delivery rates averaged about 15% annually. Postpartum hemorrhage rates were lower than published data from similar settings. Stillbirth rates ranged from 30 - 62 per 1 000 births at all facilities, higher than previously recorded by the country's population surveys. The rates of macerated stillbirths were remarkably high, close to 50% of total stillbirths, indicating severe delays in seeking or receiving emergency obstetric care. Conclusions. This study provides important benchmarks for the current burden of preventable labor- and delivery-related complications in Haiti. Surveillance data suggest an urgent need for the management of hypertensive disorders during pregnancy, timely cesarean sections for dystocia, and management and treatment of postpartum hemorrhage in Haiti. Frequent data reviews may help address facility-specific bottlenecks.